Efficacy of ultrasound therapy for the treatment of lateral elbow tendinopathy (the UCICLET Trial): study protocol for a three-arm, prospective, multicentre, randomised controlled trial. Issue 1 (17th January 2022) - Sun, Ziyang; Chen, Shuai; Liu, Weixuan; Sun, Guixin; Liu, Junjian; Wang, Jian; Wang, Wei; Zheng, Yuanyi; Fan, Cunyi
Abstract : Introduction: Lateral elbow tendinopathy (LET) is a highly prevalent disease among the middle-aged population, with no consensus on optimal management. Non-operative treatment is generally accepted as the first-line intervention. Ultrasound (US) therapy has been reported to be beneficial for various orthopaedic diseases, including tendinopathy. The purpose of this study is to investigate the efficacy of US for LET treatment. Methods and analysis: This protocol entails a three-arm, prospective, multicentre, randomised controlled trial. Seventy-two eligible participants with clinically confirmed LET will be assigned to either (1) US, (2) corticosteroid injections or (3) control group. All participants will receive exercise-based therapy as a fundamental intervention. The primary outcome is Patient-rated Tennis Elbow Evaluation. The secondary outcomes include Visual Analogue Scale for pain, shortened version of the Disabilities of the Arm, Shoulder and Hand for upper limb disability, pain free/maximum grip strength, Work Limitations Questionnaire-25 for functional limitations at work, EuroQol-5D for general health, Hospital Anxiety and Depression Scale for mental status, Global Rating of Change for treatment success and recurrence rate, and Mahomed Scale for the participant's satisfaction. Adverse events will be recorded. Intention-to-treat analyses will be used. Ethics and dissemination: Ethics committees of all clinical centres have approved this study. The leading centre is Shanghai Sixth People's Hospital, whose approval number is 2021–153. New versions with appropriate amendments will be submitted to the committee for further approval. Final results will be published in peer-reviewed journals and presented at local, national and international conferences. Trial registration number: ChiCTR2100050547.